Earth health and human health - Shah, Ashutosh; Patel, Mayur (International Journal of Research in Medical Sciences, 2024)
Climate change is the greatest threat to global health in the twenty-first century. The World Health Organization (WHO) has cautiously estimated that between 2030 and 2050, climate change could potentially result in an additional 250,000 deaths annually. There are three main ways that climate change impacts health - direct, impact mediated via ecosystem and institution mediated effect. These environmental health problems are putting extra pressure on, and eroding the capacity of, already stretched health care systems. The health sector must comprehend how climate change will affect the services it provides. It could benefit society as a whole and adjust to these climate changes. By investing in healthier buildings, going green, and implementing sustainable operations, the health sector can promote sustainability, greater health equity, and environmental health and meet the health and sustainability-related goals.